(untitled) (Journal of actual problems of jurisprudence, 2018)
This article analyses of the theoretical problems of the institute of direct democracy. The aim of the article is to consider the theoretical and legal significance of direct democracy. Institute of the direct democracy is the most important value in building a constitutional state. By fixing this kind of democracy can be implemented democracy. The paper used legal methods as analysis, comparison and historical – legal method. Key words: democracy, government, rule of law, parliamentary law, sources of law principles.